1H-MRS neurometabolite profiles and motor development in school-aged children who are HIV-exposed uninfected: a birth cohort study - Williams, Simone R.; Robertson, Frances C.; Wedderburn, Catherine J.; Ringshaw, Jessica E.; Bradford, Layla; Nyakonda, Charmaine N.; Hoffman, Nadia; Joshi, Shantanu H.; Zar, Heather J.; Stein, Dan J.; Donald, Kirsten A. (Frontiers in Neuroscience, 2023)
Objective: Alterations in regional neurometabolite levels, as well as impaired neurodevelopmental outcomes have previously been observed in children who are HIV-exposed uninfected (CHEU). However, little is known about how neurometabolite profiles may relate to their developmental impairment. The aim of this study was to compare neurometabolite concentrations in school-aged CHEU and children who are HIV-unexposed (CHU) and to explore associations of neurometabolite profiles with functional neurodevelopment in the context of perinatal HIV exposure. Methods: Single voxel proton magnetic resonance spectroscopy (1H-MRS) was used to quantify absolute and relative neurometabolites in parietal grey and parietal white matter in school-aged CHEU and aged- and community-matched CHU. Functional neurodevelopmental outcomes were assessed using the Early learning Outcome Measure (ELOM) tool at 6 years of age. Results: The study included 152 school-aged children (50% male), 110 CHEU and 42 CHU, with an average age of 74 months at the neuroimaging visit. In a multiple linear regression analysis, significantly lower absolute glutamate concentrations (Glu) and relative glutamate ratios (Glu/total creatine (Cr+PCr)) were found in CHEU compared to CHU in parietal grey matter and lower total choline to creatine ratios (GPC+PCh/ Cr+PCr) in parietal white matter. Using factor analysis and adjusted logistic regression analysis, a parietal grey matter Glu and myo-inositol (Ins) dominated factor was associated with HIV exposure status (OR 0.59, 95% CI 0.35- 0.94, p = 0.031). This factor was also found to be correlated with ELOM scores of gross motor development in CHEU.Furthermore, there was a significant association between Ins / Cr+PCr ratios in parietal white matter and ELOM scores of fine motor coordination and visual motor integration in CHEU. Conclusion: Reduced Glu concentrations in parietal grey matter may suggest regional alterations in excitatory glutamatergic transmission pathways in the context of perinatal HIV and/or antiretroviral therapy (ART) exposure, while reduced Cho ratios in parietal white matter suggests regional myelin loss. Identified associations between neurometabolite profiles and gross and fine motor developmental outcomes in CHEU is suggestive of a neurometabolic mechanism which may underlie impaired motor neurodevelopmental outcomes observed in CHEU.